Vestibular function in cochlear implant: a video-head impulse test study - Casanova, Maria Jorge (2023)
Objectives: The goal of this study is to compare semicircular canal function in high frequencies of the implanted ear before and after cochlear implantation. Study Design: Prospective study that included adults that underwent cochlear implantation, that had performed pre-operative video-Head Impulse Test (v-HIT). Material and Methods: The patients underwent new v-HIT and tonal audiometry post-surgery. Results: Seventeen patients were included in this study, with a mean age of 52 years. The hearing loss was severe in 3 cases (17,6%) and profound in 14 patients (82,4%). The mean gain of the Vestibulo-Ocular Reflex for the lateral, posterior and anterior semicircular canals on the implanted side before and after surgery varied from 0,82±0,32 to 0,82±0,29 (p=0,64, 0,5±0,25 to 0,49±0,22 (p=0,48), and 0,8±0,21 to 0,80±0,27 (p=0,93), respectively. Conclusion: This study showed good preservation of semicircular canal function though v-HIT after cochlear implantation.